Land Policy Research Development: A Bibliometric Analysis - Sinta Ningrum; Salwa Nurfaiziya (BHUMI: Jurnal Agraria dan Pertanahan)
Abstract: Research on land policy has received attention from researchers. Since the land policy was first published in 1916, research trends have continued to grow and expand. However, only some articles explain the development of issues discussed in research on land policy. Hence, this study aims to analyse bibliometric characteristics and content of papers on land policy published in Scopus-indexed journals from 1916-2023. We used protocol to analyse 1265 articles using VOSviewer. The result shows that there are five group topics discussed by scholars, namely land policy, land use, land tenure, land ownership, and China. The United States has the most publications and citations. The Chinese Academy of Science and Thomas Hartmann are recognised as institutions and authors who published most on this topic. The Land Use Policy Journal is the most essential source. China seemed to overtake US dominance in Land Policy research but was not followed by other Asian countries. There are topics for further investigation, namely land relations, land transfer, rural land, and land policy change.